Buya, Spiritual Charisma and Political Contention in West Sumatra - Abrar Abrar; Alfadli Alfadli; Yasrul Huda; Muhammad Taufik; Desip Trinanda; Ahmad Luthfy Nasri (Islam Realitas: Journal of Islamic and Social Studies, 2022)
The article unravels the roles of buyas (charismatic scholar of the community) in coping with confidence issues amongst politicians who competed in the Limapuluh Kota Regency’ 2015 Regional Election in West Sumatra. The study aims to answer the following questions: first, what are the politicians’ motives to seek audience from the buya? Second, what are rituals and statements that the buya provide? As part of a qualitative research conducted within the Regency, the data were collected through in-depth interviews to four buyas and four candidates. The interview results were then analyzed through qualitative approaches. The result of the study indicates that politicians and their canvassers performed ‘political safari’ by visiting buyas upon becoming candidate hopefuls or being pronounced candidates by the Election Committee. It is worth noting that although buyas never rejected any politician or canvasser who wished to meet them, they were never involved in direct campaigns with the candidates or canvassers. In essence, buyas provide politicians a sense of legitimacy at a time when they are losing confidence in themselves. Eventually, as in all political competitions, there will always be victors and losers.